Pengaruh Komite Audit, Kualitas Audit, dan Konservatisme Akuntansi Terhadap Tax Avoidance Dengan Kepemilikan Asing Sebagai Variabel Moderasi - Hustna Sarra; Sustari Alamsyah; Syifa Rustianti N. (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2025)
The purpose of this study was to determine the effect of audit committee, audit quality, accounting conservatism on tax avoidance with foreign ownership as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research time period used is the year from the 2019-2023 period. The population of this study in Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The sampling technique used Purposive Sampling technique. Based on the predetermined criteria, 32 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is Moderated Regression Analysis (MRA) with the help of Eviews 12.0. The results of this study indicate that audit committee, audit quality, and accounting conservatism have no effect on tax avoidance, while foreign ownership has a positive effect on tax avoidance. Foreign ownership cannot moderate the relationship between audit committee, audit quality, and accounting conservatism on tax avoidance.